SOIL AND WATER RESTORATION THROUGH BIOPORE INFILTRATION IN LANCANG GARAM VILLAGE LHOKSEUMAWE: RESTORASI TANAH DAN AIR MELALUI RESAPAN BIOPORI DI GAMPONG LANCANG GARAM KOTA LHOKSEUMAWE - Cut Azmah Fithri; Ruhalena Wilis; Yenny Novianti (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The city of Lhokseumawe frequently experiences flooding during the rainy season and waterlogging caused by rainwater. One environmentally friendly technology developed to address these issues is the biopore. Biopores are infiltration holes designed to enhance rainwater absorption and process organic waste. This technology offers various benefits, including reducing organic waste, improving soil fertility, preventing flooding, and maintaining groundwater quality. Biopores serve as an alternative solution in urban areas with limited open spaces. This community service enterprise was enforced through socialization and training styles, emphasizing the role of biopores in mitigating the urban environment. The activities involved public outreach and continued assistance in constructing biopores. These efforts aim to increase awareness of the importance of biopores, highlighting their easy, fast, and cost-effective application. The results demonstrate that biopores are an effective and sustainable approach to supporting environmental conservation.